LIFE TABLE OF PARENION BHAIRAVI POPULATION ON DIACRISIA OBLIQUA (WLK.) - SATHE, TV (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1991)
P. bhairavi S. and I, a larval parasitoid of D. obliqua was studied for its life table statistics and intrinsic rate of increase in this paper. Longevity of ovipositing females averaged 7.7 days, progeny production averaged 704 individuals with m:f offspring 1:1:24. The average period of immature stages was 19 days. The maximum mean female progeny production per day, 'mix was 12.7 on the second day. The innate capacity for increase in this parasitoid was 0.177 per female per day and population multiplied 37.89 times in mean generation time "T" of 20.53 days.